The Role of Ownership and Attention in Driving Buying Intention in E-Commerce - Hayat Yusuf; La Ode Hamida; Astil Harli Roslan (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study examines the impact of perceived review credibility on purchase intention, focusing on the mediating role of perceived belongingness and the moderating role of need for cognition. This study used a quantitative approach, using an online survey to collect data from 233 e-commerce shoppers. The study found that perceived review credibility and need for cognition significantly influenced purchase intention. Review credibility also increased the sense of belongingness, which in turn increased purchase intention. Need for cognition was found to moderate the relationship between belongingness and purchase intention, especially among individuals with a high need for cognition. Psychological factors such as need for cognition and sense of belongingness play an important role in shaping purchase intention. Marketers should focus on credible reviews and building a strong community to increase purchase intention, as well as develop effective communication strategies for consumers with a high need for cognition.